The relationship among anthropometric characteristics, stroke frequency and stroke lenght in Brazilian elite swimmers - Soares dos Santos, S.; Riehle, H. (1998)
Introduction: The 100 meter women`s freestyle swimming event was introduced at the 1912 Olympic Games. Since then the average times recorded in that race at the Olympic Games has improved about 34%, that is to say, approximately 0.33 seconds a year. Among the influences on performance in this event are physiological and biomechanical factors (Ungerechts,1979). The crucial biomechanical factors include stroke length and stroke frequency. It is also well known that there is a close relationship between these factors and the anthropometric characteristics of the body (Grimston and Hay, 1986, and Keskinen, Tilli and Komi, 1989). The aim of this paper is to determine which anthropometric characteristics most influence stroke length (SL) and stroke frequency (SF) in the 100 m freestyle race among top female Brazilian swimmers. Methods: Twenty elite Brazilian swimmers were tested. The test consisted in swimming at maximal speed for 100m in the freestyle, starting in a 25 meter pool. Fifteen meters of each 25 meter portion of the whole distance swum were filmed for each swimmer. Through the digitalization of the images in the Winanalyse System we determined medium speed, stroke length and stroke frequency. Results: SL had a negative correlation with some measures of circumference (articulation of the fist, arm, fist and Malleolus) and with the width of the thorax, and a positive correlation with some measures of height (knee, basin and Xiphoid process of the sternum). SF has a negative correlation with measures of the circumference of the knee and elbow, as well as with the length of reach, the height of the knee and of the basin, and the area of the hand. The factors that most influenced SL were the width of the trunk (24.3%) and the area of the hand (16.4%). For SF the most influential factors were the depth of the waist (22.7%) and the length of reach (14%). Conclusions: These results indicate that for the investigated swimmers, the largest SL was found in the swimmers that were thinner, taller and with larger hands. SF was found in those with shorter lower limbs, shorter reach and larger waists. References: Grimston, S. K. & Hay, J. (1986). Relationships among anthropometric and stroking characteristics of college swimmers. Med. and Sci. in Sports Exerc., Madison, 1, 60-68. Ungerechts, B. (1979). Über den Wert der Zugzahl-Ermittlung im Schwimmsport. Leistungssport, Berlin, 5, 353-356.